A Comprehensive Review of the Phytochemistry, Pharmacology and Other Applications of Euphorbiae Humifusae Herba - Jian Xiao; Hong Gu; Jiaqing Zhang; Yuqian Xue; Yunyi Chen; Weizhong Zhu; Hong Zhang; Boyi Fan; Wenli Wang (Molecules)
Euphorbiae Humifusae Herba (EHH) is a globally distributed plant commonly utilized in traditional Chinese medicine (TCM) and health food within China. The dried aerial parts of EHH are well-recognized as health foods for the management of diarrhea and other intestinal diseases. Known for its therapeutic effects, such as heat-clearing, detoxification, blood cooling, hemostasis, dampness, elimination, and jaundice relief, EHH has yielded 197 bioactive compounds identified to date, including terpenoids, flavonoids, phenolic acids, tannins, alkaloids, sterols, lactones, coumarins, and other constituents, with flavonoids and terpenoids, highlighting its wide-ranging pharmacological properties and medicinal significance. Despite its popularity in research, limited systematic and comprehensive information has been provided on the EHH. Therefore, we provide an in-depth overview of EHH, covering its botanical characteristics, traditional uses, phytochemical composition, pharmacological properties, and additional applications. Furthermore, it addresses the current challenges and limitations in modern research on EHH, offering critical perspectives to guide future studies in this field.